Genetic Association Between A Parents And Its Grandparents In Performance Traits Of Broiler Chickens - Hurea Saber Abdulrazaq (Zanco Journal of Pure and Applied Sciences)
This study aims to estimate the heredity and genetic correlations of some productive performance traits that geneticists are interested in, well as to investigate the genetic relationship between parents and grandparents of broiler chickens. Blood samples were collected from in tubes containing EDTA anticoagulant. From 240 Ross-308 birds, which were transferred directly laboratory to conduct the process of extracting DNA from blood samples. As for polymorphism, it was highest in OPA-9, where it was recorded as 13, and the percentage of polymorphism was 39.39 for the same primer. Coefficient of genetic similarity was between 0.81 - 1.00. , these characteristics were taken to compare between parents and grandparents at the age of 30 weeks in order to identify the characteristics studied when they are at the best productive age for comparison between them. It was found that there were significant differences between parents and grandparents in Egg/bird/week, Hatching, egg production, hatching all eggs (%), Chicks/Hen, where the parents recorded the highest significant difference in all of these characteristics, which was (5.90 , 5.70, 87.1 , 87.1 , 5.10 ).  respectively. Grandparents recorded a significant superiority in body weight and egg weight, which were (4064.33 and 58.5), respectively.